ANTIOXIDANT AND PHYTOCHEMICAL ANALYSIS OF METHANOL EXTRACT OF PHYLLANTHUS AMARUS (FUDMA JOURNAL OF SCIENCES, 2024)
Phyllanthus amarus is a widely recognized plant that has been traditionally utilized to cure a variety of ailments. The current study explored the phytochemical and antioxidant characteristics of P. amarus methanol extract. Standard procedures were used to analyze: 1, 1-diphenyl-2-picryl-hydrazyl (DPPH) percentage (%) inhibition, lipid peroxidation % inhibition, total phenolic content (TPC) and total flavonoid content (TFC). A higher quantity of the plant extract resulted in a greater inhibition of DPPH and lipid peroxidation percentage. The highest DPPH % inhibition (74.4%) and lipid peroxidation % inhibition (83.44%) were at 0.05 mg/ml while the lowest DPPH % inhibition (25.23%) and lipid peroxidation % inhibition (39.11%) was at 0.03 mg/ml (p < 0.05). The most prevalent compound was flavonoid, with a TFC of 460.22 µg/ml while the TPC was 7.428 µg/ml. Owing to its antioxidant and phytochemical qualities, P. amarus methanol extract may potentially find application in medicine.
Keywords: Phyllanthus amarus; phytochemicals; antioxidants; extract; total phenolic content; total flavonoid content